2022
DOI: 10.3390/biomedicines10050961
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Exosomal microRNAs and Their Targets in Papillary Thyroid Cancer Cells

Abstract: The release of molecules in exosomal cargoes is involved in tumor development and progression. We compared the profiles of exosomal microRNAs released by two thyroid cancer cell lines (TPC-1 and K1) with that of non-tumorigenic thyroid cells (Nthy-ori-3-1), and we explored the network of miRNA–target interaction. After extraction and characterization of exosomes, expression levels of microRNAs were investigated using custom TaqMan Advanced array cards, and compared with those expressed in the total cell extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Several studies have analyzed the role of miRNAs circulating in extracellular vesicles as biomarkers in thyroid cancer [26][27][28][29]. Recently, a high expression of miR-31-5p, miR-222-3p and let-7i-3p was found in exosomes isolated from TPC-1 and K1, two thyroid cancer cell lines [13] and extracellular vesicles isolated from thyroid tissue after BRAFV600E activation [30]. Exosomes naturally released from distinct cell types can also have beneficial effects in several human diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have analyzed the role of miRNAs circulating in extracellular vesicles as biomarkers in thyroid cancer [26][27][28][29]. Recently, a high expression of miR-31-5p, miR-222-3p and let-7i-3p was found in exosomes isolated from TPC-1 and K1, two thyroid cancer cell lines [13] and extracellular vesicles isolated from thyroid tissue after BRAFV600E activation [30]. Exosomes naturally released from distinct cell types can also have beneficial effects in several human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, we published results related to the characterization of Nthy-ori 3.1 and TPC-1 cell-derived exosomes by Dynamic Light Scattering (DLS) analysis and Western blotting analysis [13]. From the DLS analysis, we found that exosomes had a size distribution in the expected range of 40-160 nm.…”
Section: Gene Expression Analysis Of Papillary Thyroid Cancer and Non...mentioning
confidence: 93%
See 1 more Smart Citation
“…Identifying EV-miRNA targets and studying miRNA-mRNA networks in a global and unbiased manner greatly benefited from the development of bioinformatics tools. A comparison of the profile of EV-miRNAs released by two thyroid cancer cell lines with that of non-cancerous thyroid cells revealed a differential abundance of five miRNAs (miR-21-5p, miR-31-5p, miR-221-3p, miR-222-3p, and let-7i-3p) in EVs of tumor cells, with three of them (miR-31-5p, miR-222-3p, and let-7i-3p) being more abundant in EVs from the more aggressive cancer cells [ 41 ]. These miRNAs were also present in EVs isolated from thyroid tissue after BRAF V600E induction [ 22 ].…”
Section: Evs In Tcmentioning
confidence: 99%
“…These miRNAs were also present in EVs isolated from thyroid tissue after BRAF V600E induction [ 22 ]. Functional enrichment and network analysis of these miRNAs’ target genes (ICAM1, FOXO3, SELE, ETS1, RECK, PTEN, and TIMP3) are regulators of these miRNAs from aggressive thyroid cancer cells of the tumor microenvironment through modulation of angiogenesis and immune response [ 41 ].…”
Section: Evs In Tcmentioning
confidence: 99%